PENGARUH KERAGAMAN PRODUK, HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA DUTA MINIMARKET MIMBAAN SITUBONDO - Ediyanto, Ediyanto (Growth, 2022)
This study uses statistical applications. The population in this study were customers who visited Duta Minimarket Mimbaan Situbondo. The sample used was 99 respondents and used a simple random sampling method. Data collection was carried out using a questionnaire. The data analysis technique used in this study is multiple linear regression analysis. The results of the t test show that all the independent variables (product variety, price, location) have a positive effect on the dependent variable, namely repeat purchases. Multiple linear regression analysis shows that Y = -1.005 E-16 + 0.290 X1 + 0.346 X2 + 0.404 X3 + e. The standard error is 0.080, meaning that all variables calculated in the SPSS version 22 test for Windows 10 have a confounding variable level of 0.080. The results of the t test, tcount product diversity (2.042), price (3.594) and location (4.447). The diversity of products, prices and locations have a partial effect on customer satisfaction tcount > ttable. The results of the F test show Fcount > Ftable, namely 19.855 > 2.70. The coefficient of determination (adjusted R2) obtained is 0.385. This means that 38.5% of consumer satisfaction is influenced by product variety, price and location variables. The remaining 61.5% is influenced by other variables.